Potret Implementasi e-Government pada Layanan Publik Pengaduan Masyarakat di Indonesia - Yunita, Novi Prisma; Selina, Refdian Shella; Anggriawan, Galih (AI Society & STMIK Indonesia, 2024)
Public complaints are a form of public services provided by governments. Its function is to facilitate the public in submitting complaints related to public services. Public complaint channels: SMS, telephone number, email, form, and website. Based on website searches, various implementations of complaints were found in government websites. They are vary in term of number and implementation. For example, one website provides 2 channel, other website provides none. Two website provide 2 channel, but differs in attributes. Apart of this diversity, the portrait of implementing public complaints is unexplored. This research aims to map the implementation of public complaints in provincial governments in Indonesia. Official website is used as primary data. Documentation and website analysis is conducted to each websites. Keywords, such as complaints, complaints, public services, and public complaints, are used in website content analysis. The content analysis is classified into the Gartner stage model: presence, interaction, transaction, and transformation. The results show that of the 38 provincial governments, 6 provincial governments are at the presence stage, 23 at the interaction stage, 4 at the transaction stage, and 5 provincial governments at the transformation stage.